2019
DOI: 10.1177/1468087419851905
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a zonal hybrid URANS/LES turbulence modeling method for multi-cycle engine flow simulation

Abstract: A zonal hybridization of the RNG [Formula: see text]-[Formula: see text] URANS model is proposed for the simulation of turbulent flows in internal combustion engines. The hybrid formulation is able to act as URANS, DES or LES in different zones of the computational domain, which are explicitly set by the user. The resulting model has been implemented in a commercial computational fluid dynamics code and the LES branch of the modified RNG [Formula: see text]-[Formula: see text] closure has been initially calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 65 publications
0
26
0
2
Order By: Relevance
“…where ∆ is a grid-related filter length scale and C DES ≈ O(1). The ∆ parameter is calculated as the cubic root of the computational cell volume, while C DES is set to 0.61 [27]. As stated above, the expressions (5) and 6are general and can be applied to any URANS form, by just adapting l RANS accordingly.…”
Section: Turbulence Modeling 21 Standard and Consistent Rng K-ε Des mentioning
confidence: 99%
See 2 more Smart Citations
“…where ∆ is a grid-related filter length scale and C DES ≈ O(1). The ∆ parameter is calculated as the cubic root of the computational cell volume, while C DES is set to 0.61 [27]. As stated above, the expressions (5) and 6are general and can be applied to any URANS form, by just adapting l RANS accordingly.…”
Section: Turbulence Modeling 21 Standard and Consistent Rng K-ε Des mentioning
confidence: 99%
“…The bore × stroke values are equal to 92 × 86mm, with a (nominal) compression ratio of 10:1. This engine has already been the object of extensive numerical studies by the authors [26,27,35,36], in which the zonal hybrid methodology shown above has been implemented into the STAR-CD software [37] and then assessed and validated on a relatively fine computational grid (2×10 6 elements at the BDC). Nonetheless, a head-to-head comparison between the DES and DESx modes of operation was still missing and is, therefore, proposed here.…”
Section: Zonal-des Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this panorama, a crucial role is played by CFD analyses which allow to reduce time-and cost-to-market thanks to a proper prediction of the knock onset. Simulations are based, on the one hand, on reliable knock models [12][13][14][15][16] and, on the other hand, on a robust numerical framework able to fairly reproduce flow field, cycle-to-cycle variability, heat transfer, spray, film formation, fuel chemistry and combustion [17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Broadly speaking, a hybrid URANS/LES method should be based on the ability to adapt its behavior by applying the best-fitting modeling option with respect to the available numerical resolution. In the past 10 years, the number of engine-related hybrid modeling applications has been constantly increasing [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], but hybrid/LP investigations are almost absent [27,28]. In our study, we evaluated two previously developed hybrid scale-resolving approaches [21,24,28,29] for a computational analysis of the "Spray G" reference GDI injector [30].…”
Section: Introductionmentioning
confidence: 99%